ON ALGEBRAIC AND ANALYTIC CORE II
In this paper, we continue the study of the algebraic core spectrum and the analytic core spectrum of an operator T on the complex Banach space X: σalc(T) = λ ∈ \(C\) : C(λI− T ) = 0 and σac(T) = λ ∈ \(C\) : K(λI− T ) = 0 where C(T) and K(T) are respectively the algebraic core and the analytic core for T. We shall be concerned with the relations between σac(·) (σalc(·)) and diﬀerent classical parts of spectrum: the point spectrum, the approximate point spectrum, the surjectivity spectrum and the Kato spectrum. Moreover, some applications are given. , journal=Italian Journal of Pure and Applied Mathematics, author=Tajmouati, Abdelaziz and El Bakkali, Abdeslam and Karmouni, Mohamed, year=2015, month=Jun., pages=171–180